Mapping small DNA sequences by fluorescence in situ hybridization directly on banded metaphase chromosomes. - Fan, Y S (1990)
A procedure for mapping small DNA probes directly on banded human chromosomes by fluorescence in situ hybridization has been developed. This procedure allows for the simultaneous visualization of banded chromosomes and hybridization signal without overlaying two separate photographic images. This method is simple and rapid, requires only a typical fluorescence microscope, has proven successful with DNA probes as small as 1 kilobase, is applicable for larger probes, and will greatly facilitate mapping the vast number of probes being generated to study genetic disease and define the human genome. Human metaphase chromosomes were prepared from phytohemagglutinin-stimulated lymphocyte cultures synchronized with bromodeoxyuridine and thymidine. Probes were labeled with biotin-dUTP, and the hybridization signal was amplified by immunofluorescence. Chromosomes were stained with both propidium iodide and 4',6-diamidino-2-phenylindole (DAPI), producing R- and Q-banding patterns, respectively, allowing unambiguous chromosome and band identification while simultaneously visualizing the hybridization signal. Thirteen unique DNA segments have been localized to the long arm of chromosome 11 by using this technique, and localization of 10 additional probes by using radioactive in situ hybridization provides a comparison between the two procedures. These DNA segments have been mapped to all long-arm bands on chromosome 11 and in regions associated with neoplasias and inherited disorders.